2009
DOI: 10.3324/haematol.2008.005272
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of NOTCH1 and FBXW7 mutations in adult acute T-lymphoblastic leukemia

Abstract: BackgroundNOTCH1 mutations have been associated with a favorable outcome in pediatric acute Tlymphoblastic leukemia. However, the results of studies on the prognostic significance of NOTCH1 mutations in adult T-lymphoblastic leukemia remain controversial. Design and MethodsHere we have investigated the prognostic impact of mutations in the NOTCH1 pathway, in particular, the NOTCH1 and FBXW7 genes, in a large cohort of adult patients with Tlymphoblastic leukemia (n=126). We determined the occurrence of mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
3
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 36 publications
4
55
3
1
Order By: Relevance
“…[42][43][44][45] Similarly, controversial results on the prognostic effect of NOTCH activation have been obtained in adult T-ALL. [46][47][48][49] These inconsistent results might at least in part be explained by the prognostic relevance of functional interplay between specific genetic lesions in T-ALL, as recently shown for NOTCH1 activation and inactivation of PTEN in children with T-ALL treated according to Berlin-Frankfurt-Munster study protocols. 50 In our study, both univariate and multivariate analyses revealed that patients whose leukemias showed mutations in NOTCH1 and/or FBXW7 had a favorable outcome.…”
Section: Discussionmentioning
confidence: 90%
“…[42][43][44][45] Similarly, controversial results on the prognostic effect of NOTCH activation have been obtained in adult T-ALL. [46][47][48][49] These inconsistent results might at least in part be explained by the prognostic relevance of functional interplay between specific genetic lesions in T-ALL, as recently shown for NOTCH1 activation and inactivation of PTEN in children with T-ALL treated according to Berlin-Frankfurt-Munster study protocols. 50 In our study, both univariate and multivariate analyses revealed that patients whose leukemias showed mutations in NOTCH1 and/or FBXW7 had a favorable outcome.…”
Section: Discussionmentioning
confidence: 90%
“…Some studies suggest an improved early response to therapy and prognosis in these patients, although others lack prognostic 21,329 although a trend toward improved EFS was seen in one (P ¼ .10). 21 In pediatric T-ALL, one study identified an improved early response to therapy (P , .01), decreased early (FBXW7 and/or NOTCH1) and late MRD (NOTCH1, P , .01), and improved EFS (NOTCH1; P ¼ .01).…”
Section: 323mentioning
confidence: 99%
“…Most recently, for the group of ETP-ALL a mutational spectrum similar to acute myeloid leukemia (AML) was observed [6,7].ETP-ALL patients show less frequent NOTCH 1 mutations (15 %) [8,9] and a high rate of FLT-3 mutations (35 %). Even among ETP-ALL patients, patients with a FLT3 mutation show a distinct immunophenotype with positivity for CD117, CD34, CD13 and CD2.…”
Section: Introductionmentioning
confidence: 99%